Pengaruh Model Pembelajaran Kooperatif Tipe Group Investigation (GI) Terhadap Hasil Belajar Fisika Ditinjau dari Gaya Belajar Siswa - Siska Widiawati; Hikmawati Hikmawati; Wahyudi Wahyudi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
This research is aimed to tests (1) the effect of cooperative model learning in group investigation (GI) type toward the students learning physics result observed from studentsÃ¢â¬â¢ learning technique, (2) the effect of students learning strategy toward studentsÃ¢â¬â¢ learning physics result, (3) the interaction of cooperative model learning in group investigation (GI) type toward students learning strategy toward students learning physics result. This type of research is quasi experiment with factorial design ÃÂ research program. The population of this research is all of the XI IPA class of SMAN 8 Mataram. The source sample of this research is using cluster random sampling technique.ÃÂ  Hence, XI IPA 3 class has been chosen as experiment class and XI IPA 5 as control class. The collecting data of studentsÃ¢â¬â¢ learning result done by using multiple choice questions with 74.1 mean score of experiment class and 65,4 mean score for control class and measure studentsÃ¢â¬â¢ learning strategy by giving learning strategy questionnaire. Hypothesis tested using ANAVA two ways with 5% significant standard. The result of first hypothesis shows that 22,85 for fcount that bigger than 4,03 ftable means that there is a effect of cooperative model learning in group investigation (GI) type toward studentsÃ¢â¬â¢ learning physics result. While the second hypothesis shows that 25,05 fcount bigger than 4,03 ftable there is a effect of cooperative model learning in group investigation (GI) type toward studentsÃ¢â¬â¢ learning physics result. Last, hypothesis shows that 4,57 fcount bigger than 3,18 ftable means there is an the interaction of cooperative model learning in group investigation (GI) type toward studentsÃ¢â¬â¢ learning strategy toword students realning physics result.